Effectiveness of Legal Protection in Preventing Intellectual Property Infringement by Micro and Small Enterprises - Widarsadhika, Rahadyan; Michael, Tomy; Sihasale, Giovanni Gianini; Mauliddiyah, Andyka Tahta; Rahma, Andien Aisyah Nur (CV. ULIL ALBAB CORP, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia's economy, yet they often face challenges in protecting their intellectual property rights (IPR), particularly trademarks. This study aims to analyze the effectiveness of legal protection for trademarks owned by MSMEs and identify the barriers they encounter. Employing a normative juridical approach combined with empirical research, data were collected through document analysis, interviews, and surveys involving MSME actors in Surabaya and Mojokerto. The results reveal that despite the existence of comprehensive IPR regulations, the effectiveness of trademark protection remains limited. Key obstacles include a lack of understanding among business actors, complex registration procedures, and insufficient legal literacy. Survey findings show that over 50% of respondents perceive inadequate knowledge as the main barrier to trademark protection, followed by procedural complexities. Although costs were less of a concern, many MSMEs still fail to register their trademarks, leaving them vulnerable to infringement. This study concludes that while Indonesia’s legal framework for IPR is well-established, its implementation requires significant improvement through enhanced education, streamlined procedures, and strengthened enforcement. Strengthening these aspects is essential to empower MSMEs, encourage innovation, and boost their competitiveness both domestically and internationally.